New record of Hergovitsia Bucsek from Cambodia (Lepidoptera, Erebidae, Arctiinae, Lithosiini), with description of a new species - Bayarsaikhan, Ulziijargal; Bucsek, Karol; Bae, Yang-Seop (Zootaxa, 2018)
The genus Hergovitsia Bucsek (2012) is reported for the first time in Cambodia, for the new species, Hergovitsia longivirga n. sp. A diagnostic comparison is made with Hergovitsia magnifica Bucsek, 2012. Illustrations of adults and genitalia of the new and all known species are provided, with a key to the genus Hergovitsia on the basis of the external morphology and male genitalia.